New taxa and notes on bark and bush crickets (Orthoptera, Grylloidea, Gryllidae, Landrevinae and Podoscirtinae) from Sabah - Tan, Ming Kai; Japir, Razy; Chung, Arthur Y.c.; Robillard, Tony (Zootaxa, 2022)
From the eastern parts of Sabah, four new species of crickets are described, two of which are from the subfamily Landrevinae and two from the subfamily Podoscirtinae: Duolandrevus (Duolandrevus) nobilis sp. nov. and Odontogryllodes spinifer sp. nov.; and Brevimunda trilineata sp. nov. and Varitrella (Cantotrella) tabin sp. nov., respectively. We also describe the calling songs for three species: Duolandrevus (Bejorama) lambir Gorochov, 2017, Duolandrevus (Duolandrevus) nobilis sp. nov. and Varitrella (Cantotrella) tabin sp. nov. A new locality record (Sabah, Sepilok) for Duolandrevus (Bejorama) lambir Gorochov, 2017, previously known from western Borneo (Sarawak, Lambir Hill and Brunei Darussalam, Kuala Belalong), was also reported.